(untitled) (TEMU ILMIAH NASIONAL PERSAGI, 2023)
Red beans are a useful source of fiber as a mixture of food products. The addition of red beans to ice cream is easy and practical and the fiber content is 4 g in 100 g of red beans. So that ice cream with the addition of red beans can overcome obesity. The purpose of this study was to calculate fiber levels in ice cream with red bean substitution (Phaseolus vulgaris L.). The fiber content of ice cream is calculated using a calculator by multiplying the net weight of raw red beans by the fiber content of red beans in the Indonesian food composition table and then divided by 100. This type of research is pre-experimental research or pre-experimental designs with one group post test desaign. The results of the calculation of the fiber content of ice cream with the substitution of red beans showed that 1 ice cream recipe with a concentration of 15 percent has a fiber content of 1.47 g then a concentration of 10 percent has a fiber content of 1.01 g and a concentration of 5 percent has a fiber content of 0.67 g. Advice to subsequent researchers for higher fiber levels.